Kemungkinan keterdapatan hidrokarbon di Cekungan Bengkulu - Rachmat Heryanto (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no3.20071The Bengkulu Basin is known as a typical fore-arc basin, situated in the southwest of Sumatera Island. The basin was occupied by the Eo-Oligocene equivalent Lahat Formation that is unconformably overlain by the Oligocene-Miocene volcanic rock of Hulusimpang Formation. It is then succeeded by siliciclastics and few carbonates of Early-Middle Miocene Seblat Formation. Unconformably overlies the Seblat Formation is siliciclastics of the Middle-Late Miocene Lemau Formation, followed by the Late Miocene-Pliocene Simpangaur Formation. The deposition was ended by a typical volcanic rock of the Bintunan/Ranau Formation. The results of sedimentary rock and organic petrographic, scanning electron microscopic and geochemistry (TOC & rock-eval and gas chromatography) analyses conducted on several selected surface outcrop samples and some oil seepage samples collected during the field work, indicate that hydrocarbon is possibly present in the Bengkulu Basin. A source rock possibly occurs in fine-grained carbonaceous sediments of the Seblat and Lemau Formations. The reservoir rock is possibly the sandstone bed of the Lemau Formation and the sandstone and limestone beds of the Seblat Formation. The caprock is a claystone bed present within the Seblat Formation as well as in the Lemau Formation. The hydrocarbon trap probably occurs as stratigraphic and structural types.